Improving of Sensitivity of PbS Quantum Dot Based SWIR Photodetector Using P3HT - Kyeong-Ho Seo (Materials, 2021)
In this study, we improved the photosensitivity of the lead sulfide quantum dot (PbS QD)-based shortwave infrared (SWIR: 1.0–2.5 μm) photodetector by blending poly(3-hexylthiophene-2,5-diyl) (P3HT) with PbS QD. The PbS QD used for SWIR photoactive layer showed an absorption peak at 1410 nm. In addition, by using zinc oxide nanoparticles (ZnO NPs) as an interlayer, we obtained the stable current characteristics of our device. To confirm the effectiveness of P3HT on the PbS QD-based SWIR photodetector, we compared the electrical characteristics of a PbS QD-based device with a hybrid P3HT:PbS QD-based device. In the reverse bias region, the current on/off ratio of the PbS QD-based device was 1.3, whereas the on/off ratio of the hybrid P3HT:PbS QD-based device was 2.9; 2.2 times higher than the PbS QD-based device. At −1 V, the on/off ratio of the PbS QD-based device was 1.3 and the on/off ratio of the hybrid P3HT:PbS QD-based device was 3.4; 2.6 times higher than the PbS QD-based device. The fabricated P3HT:PbS QD-based device had the highest on/off ratio when −1 V voltage was applied.